ANALISIS ENERGY SECURITY BERDASARKAN EFISIENSI ENERGI TERHADAP PRODUKTIVITAS ENERGI PADA PABRIK PALM KERNEL OIL PT. PERKEBUNAN NUSANTARA V TANDUN ROKAN HULU - Fithra, Dwi Youmu; Daulay, Iwan Nauli; ', Samsir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the level of energy security based on energy efficiency which is conductedin the Palm Kernel Oil Plant Tandun PT. PTPN V. By using Slovin formula, the number of samples taken in the amount of 66 respondents who are all employees of the Plant. Data analysis method used is descriptive analysis. These results indicate that the Energy Security is based on energy efficiency is efficient and saving on energy productivity at the Palm Kernel Oil Plant Tandun PT. PTPN V. From the research result company should further improve biogas and minimize diesel consumption.Keywords : energy security, energy efficiency, and energy productivity.